Determinants of routine immunization program in Nepal. - Thapa, Kanchan (2019)
ABSTRACT: National immunization program is priority first (P1) program of the government of Nepal. The huge progress in reduction of child morbidity and mortality is possible through the most powerful public health intervention i.e. immunization. The present study has aimed to explore the determinants of immunization in Nepal based on DHS data set of 2016. The study has considered children aged under five for analysis. Descriptive as well as analytical statistics such as bivariate and multivariate analysis has been used for exploring the relationship. Those variables which are significant at p<0.05 are taken to backward logistic regression. The adjusted odds ratio (aOR) has been computed. The models for enabling resources, predisposing factors and external environment has been explored along with chi square value and respective p-value for model. The socio-demographic variables, health services variables, card retention status, and immunization status are included in the analysis. The study results show that full immunized children are 23 percent in province, 46 percent are from villages, male children 54 percent. The mothers having 4 or no visit are 8 times likely to have drop out of DPT 1 Vs 3 vaccine. Similarly, mothers who delivered at health facilities are nearly twice as likely to have HBR card retention. Age appropriate vaccination for BCG is 74 percent in the rich and middle family. Mothers with 4 and more ANC visits were aOR 2.170 (1.351-3.86), mothers who use the internet less than once a week aOR 1.932 (1.205-3.099) have age appropriate BCG vaccination. Similarly, mothers with less than 4 ANC visits aOR 7.945 (4.070-15.511) had to drop out. Mothers who have gone for 4 and more ANC visit kept HBR card safely aOR 1.656 (1.066-2.575) than who do not go for ANC visit. Women who delivered at health facilities kept HBR more safely aOR1.812 (1.210-2.713) than those with home deliveries. Those mothers who have gone for 4 & more ANC visit were more likely aOR=2.17(1.35-386) to have age appropriate BCG vaccination. Similarly children from province 2 are 88 percent less likely to get BCG on time as compared to province 1 children. Mothers who uses internet less than once a week are more likely to have BCG on time aOR 2.17 (1.353.86). The present study concludes that immunization status depends on the external environment, enabling resources and predisposing factors. Educated parents are aware of the importance of the HBR card, complete immunization, and age-appropriate vaccination. ANC, PNC visits, wealth index and access to information are more contributing factors for better immunization status. The present study has recommended further study based on primary data on large scale focusing on age appropriate vaccination. The policy maker should replicate the present findings for better immunization program in Nepal.